UK and Canadian Gulf War Veteran Mortality: Using A Fellow Military Cohort as a Comparison Population. (2018) - Rolland-Harris, Elizabeth; Harrison, Kate; Simkus, Kristen; Baird, Lisa; Palmer, Kate; Sandra, Dear; VanTil, Linda
No abstract available